2015
DOI: 10.4300/jgme-d-14-00516.1
|View full text |Cite
|
Sign up to set email alerts
|

Mastery of Status Epilepticus Management via Simulation-Based Learning for Pediatrics Residents

Abstract: Background Management of status epilepticus (SE) in the pediatric population is highly time-sensitive. Failure to follow a standard management algorithm may be due to ineffective provider education, and can lead to unfavorable outcomes. Objective To design a learning module using high-fidelity simulation technology to teach mastery achievement of a hospital algorithm for managing SE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…For instance, gastroenterology fellows who practiced on a colonoscopy simulator rather than patients performed as well during actual patient colonoscopies as fellows who had already performed 80 procedures on actual patients. 7 Simulation-based mastery learning has been used to improve skills in diverse clinical areas, including endof-life discussions, 28 cardiac auscultation, 29 management of pediatric status epilepticus, 30 advanced cardiac life support, 18 and laparoscopic surgery, 31 and has also been shown to reduce patient complications, 12,14,[32][33][34] decrease length of hospital stay, 33 and reduce hospital costs. 35,36 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, gastroenterology fellows who practiced on a colonoscopy simulator rather than patients performed as well during actual patient colonoscopies as fellows who had already performed 80 procedures on actual patients. 7 Simulation-based mastery learning has been used to improve skills in diverse clinical areas, including endof-life discussions, 28 cardiac auscultation, 29 management of pediatric status epilepticus, 30 advanced cardiac life support, 18 and laparoscopic surgery, 31 and has also been shown to reduce patient complications, 12,14,[32][33][34] decrease length of hospital stay, 33 and reduce hospital costs. 35,36 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of self-efficacy was first described in the 1970s as an individual’s belief in her capability to organize and execute a plan to manage future situations [ 7 ]. Self-efficacy predicts academic performance in medical students [ 7 ] and is correlated with resident performance in simulated patient care scenarios [ 8 ]. While self-efficacy levels are not without limitations in correlating to performance [ 9 , 10 ], use of LURIES increased the resident perception of self-efficacy and comfort with patient management while caring for patients overnight, discussing management plans with parents and nursing staff, and anticipating acute events, leading to widespread use of the tool.…”
Section: Discussionmentioning
confidence: 99%
“…Brain death determination simulations have also raised awareness regarding the incompetence of many physicians who perform the determination. As a corollary, a study investigating mastery of status epilepticus management for pediatric residents found that prior to the intervention, none of the residents achieved satisfactory performance as measured by an observational checklist of required action items, but all met mastery standards following the intervention [85].…”
Section: Task Trainersmentioning
confidence: 99%